2013
DOI: 10.1158/1535-7163.mct-12-0492
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Targeting of COX-2 and AKT Using Selenocoxib-1-GSH to Inhibit Melanoma

Abstract: Melanoma is a highly metastatic and deadly disease. An agent simultaneously targeting COX-2, PI3K/Akt and MAPK signaling pathways that are deregulated in up to 70% of sporadic melanoma might be an effective treatment but no agent of this type exists. To develop a single drug inhibiting COX-2 and PI3K/Akt signaling (and increasing MAPK pathway activity to inhibitory levels as a result of Akt inhibition), a selenium-containing glutathione (GSH) analog of celecoxib, called selenocoxib-1-GSH was synthesized. It ki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 45 publications
1
59
0
Order By: Relevance
“…Melting points (mp) were determined with a Mettler FP82ϩFP80 apparatus (Greifense, Switzerland) and are not corrected. The 1 H nuclear magnetic resonance (NMR) and 13 C NMR spectra were recorded on a Bruker 400 Ultrashield spectrometer (Rheinstetten, Germany) using TMS (tetramethylsilane) as the internal standard. The infrared (IR) spectra were obtained on a Thermo Nicolet FT-IR Nexus spec- trophotometer with KBr pellets.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Melting points (mp) were determined with a Mettler FP82ϩFP80 apparatus (Greifense, Switzerland) and are not corrected. The 1 H nuclear magnetic resonance (NMR) and 13 C NMR spectra were recorded on a Bruker 400 Ultrashield spectrometer (Rheinstetten, Germany) using TMS (tetramethylsilane) as the internal standard. The infrared (IR) spectra were obtained on a Thermo Nicolet FT-IR Nexus spec- trophotometer with KBr pellets.…”
Section: Methodsmentioning
confidence: 99%
“…Their purity was assessed by TLC and elemental analyses, and their structures were identified from spectroscopic data. IR, 1 H NMR, 13 C NMR, mass spectrometry, and elementary analysis methods were used for structure elucidation (Fig. 2).…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The major substrate of PTEN is phosphatidylinositol-3, 4, 5-triphosphate (PIP3), which is produced by the action of phosphoinositide-3-kinase (PI3K) [10]. The PI3K/AKT signaling pathway plays an important role in the development of resistance to carcinoma therapy, and inhibition of the PI3K/AKT signaling pathway may suppress cancer cell growth and induce apoptosis in various cancers [11][12][13]. PTEN is the main negative regulator of the PI3K/AKT signaling pathway and is implicated in regulating proliferation and survival of T-cell progenitors [14].…”
Section: Introductionmentioning
confidence: 99%
“…Using a combination of protein arrays and systems biology followed by validation studies, leelamine was found to inhibit the PI3K/Akt, STAT3 and MAPK pathways by disrupting cancer cell cholesterol transport. These are key driver pathways in melanoma cells constitutively activated in 50 to 70% of melanomas, functioning to reduce cellular apoptosis, increase proliferation and aid the invasive processes promoting melanoma progression (14-16). …”
Section: Introductionmentioning
confidence: 99%